Shade improves seedling quality of ornamental Cyclocarya species under plastic greenhouse cultivation - Ying Feng; Limei Zhi; Hongyun Pan; Yongshan Chen; Jinghua Xu (Ornamental Plant Research, 2023)
Plastic greenhouse cultivation is a widespread and convenient way of cultivating high-quality seedlings, which are often damaged by higher temperatures during summer. Cyclocarya paliurus, a medical and ornamental species with low-quality seedlings, was investigated using three shading levels (treatment with no shade net (SH0), treatment with one layer of shade net (SH1), and treatment with two layers of shade net (SH2)). The growth and physiological responses of seedlings under plastic greenhouse cultivation were investigated from June to September. The results showed that the survival rate of seedlings reached 100%, and seedling growth and biomass were the best under SH2, with higher plant height and leaf area than that under other treatments. Water content of seedlings exhibit not difference between three shading levels, and leaves had the highest water content and total soluble sugar content. The chlorophyll content in the leaf increased, but malondialdehyde content decreased with increasing shading layers. Mineral content were in the following order: calcium > potassium > magnesium > sodium, and the translocation factor decreased with increasing shading layers. Antioxidant enzyme activities were in the following order: SOD > PPO > POD > CAT; their activities decreased with increasing shading layers, except for that of PPO. Various correlation existed between physiological response and seedling growth. Shade improved seedling quality through a series of physiological responses under plastic greenhouse conditions. This study provides a solid foundation for greenhouse cultivation of Cyclocarya species.